1975
DOI: 10.1016/s0010-9452(75)80015-3
|View full text |Cite
|
Sign up to set email alerts
|

Go - No Go Learning After Frontal Lobe Lesions in Humans

Abstract: 48 patients with unilateral frontal or non-frontal cortical lesions were given a go - no go learning task. Patients with frontal lesions in either hemisphere took longer to learn the task and made more false "go" responses than control patients. They also, unlike controls, took longer to make in correct positive responses than correct positive ones. Medial frontal lesions were found to be particularly important in giving rise to poor performance on this task. It is suggested that this task is non-unitary in na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
147
0
4

Year Published

1987
1987
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 314 publications
(165 citation statements)
references
References 7 publications
7
147
0
4
Order By: Relevance
“…Monkeys with lesions in the inferior prefron tal convexity display impaired drive inhibition (Iversen and Mishkin, 1970). Furthermore, patients with lesions of the orbitomedial prefrontal cortex display a reduced ability to suppress interference from internal and external stimuli (Drewe, 1975;Stuss et aI., 1982;Fuster, 1985). Finally, the orbi tofrontal and dorsal prefrontal cortices have been suggested to be important for the temporal organi zation of behavior and cognition (Fuster, 1984(Fuster, , 1985Ingvar, 1985).…”
Section: Resultsmentioning
confidence: 99%
“…Monkeys with lesions in the inferior prefron tal convexity display impaired drive inhibition (Iversen and Mishkin, 1970). Furthermore, patients with lesions of the orbitomedial prefrontal cortex display a reduced ability to suppress interference from internal and external stimuli (Drewe, 1975;Stuss et aI., 1982;Fuster, 1985). Finally, the orbi tofrontal and dorsal prefrontal cortices have been suggested to be important for the temporal organi zation of behavior and cognition (Fuster, 1984(Fuster, , 1985Ingvar, 1985).…”
Section: Resultsmentioning
confidence: 99%
“…The order of the two conditions between sessions was also counterbalanced. The study and recognition phases were separated by a 10-minute delay that was filled with two non-verbal cognitive tasks: the Dragons' House test of flexibility from Zimmermann, Gondan, and Fimm's (2005) attentional test battery for children KiTAP, and the Matrix subtest of the Wechsler Preschool and Primary Scale of Intelligence (Wechsler, 2004, Running head: Distinctiveness heuristic in children 8 2005) for one session; the self-ordered pointing test (SOPT), which assesses the executive ability to generate and monitor a sequence of responses (Cragg & Nation, 2007) and a go/no-go test of response inhibition (Drewe, 1975) for the other session.…”
Section: Methodsmentioning
confidence: 99%
“…Neuroanatomical studies of humans, non-human primates and rodents have pinpointed regions of the frontal cortex and basal ganglia that are critical for action inhibition, and interplay between these regions may be essential for attaining appropriate behavioural outcomes (Band and van Boxtel 1999). Early primate studies showed that lesions of the inferior convexity, a likely homologue in macaques of the right inferior frontal gyrus in humans, produced impairments in go/no-go performance (Iversen and Mishkin 1970), and in human studies, the go/no-go task has revealed actionrestraint deficits following frontal cortical damage (Decary and Richer 1995;Drewe 1975;Godefroy and Rousseaux 1996). Recent studies have highlighted several cortical regions of interest with respect to both stop-signal and go/ no-go tasks, in particular the inferior frontal cortex (IFC).…”
Section: Neural Systems Underlying Action Restraint and Action Cancelmentioning
confidence: 99%